Comparison of two species-specific oscillometric blood pressure monitors with direct blood pressure measurement in anesthetized cats - Cerejo, Sofia A. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Garofalo, Natache A. [UNESP]; Rodrigues, Jéssica C. [UNESP]; Celeita-Rodríguez, Nathalia [UNESP]; Lagos-Carvajal, Angie P. [UNESP] (Wiley, 2017)
Objective: To compare the performance of 2 species-specific oscillometric blood pressure (OBP) monitors (petMAPclassic and petMAPgraphic) with direct blood pressure measurement in anesthetized cats. Design: Prospective, experimental study. Setting: Veterinary teaching hospital. Animals: Eight adult cats (3.2–5.5 kg). Interventions: During isoflurane anesthesia, OBP cuffs were placed on the thoracic limb and on the base of the tail while invasive blood pressure (IBP) was recorded from a dorsal pedal artery. End-tidal isoflurane concentrations, with or without intravenous dopamine (n = 8), norepinephrine (n = 1), or phenylephrine (n = 1) were adjusted to change invasive mean arterial pressure (MAP) between 40 to 100 mm Hg. Data were analyzed by the Bland-Altman method and 4-quadrant plots. Measurements and Main Results: Mean biases and limits of agreement (LOA: ± 1.96 SD) (mm Hg) recorded between the petMAPclassic (thoracic limb) and IBP for systolic arterial pressure (SAP), diastolic arterial pressure (DAP), and MAP were 4.2 ± 28.5, −6.1 ± 13.2, and −1.9 ± 14.6, respectively; mean biases and LOA (mm Hg) recorded with the tail cuff were 7.2 ± 31.3 (SAP), −6.1 ± 11.6 (DAP), and −1.1 ± 11.7 (MAP). Mean biases and LOA (mm Hg) between petMAPgraphic (thoracic limb) and IBP were 7.7 ± 27.0 (SAP), −4.3 ± 11.5 (DAP), 0.2 ± 13.0 (MAP); values recorded with the tail cuff were 10.9 ± 29.6 (SAP), −4.4 ± 11.7 (DAP), and −0.1 ± 12.1 (MAP). Concordance rates after excluding arterial pressure changes ≤ 5 mm Hg was ≥ 93% for both devices. Conclusions: Although both OBP monitors provide unacceptable SAP estimations, MAP values derived from both monitors and DAP measured by the petMAPgraphic result in acceptable agreement with the reference method according to the Association for the Advancement of Medical Instrumentation (mean bias ≤ 5 mm Hg with LOA ≤ ± 16 mm Hg). Both monitors provide acceptable trending ability for SAP, DAP, and MAP.
Keywords: anesthesia; blood pressure; feline; noninvasive pressure